Diseño sísmico por desempeño en Colombia - Gallego, Mauricio (Revista de Ingeniería, 2001)
Future necessity of implement several levels of design is established. The most important variables which defined the behavior of structures under seismic actions are identified and their influence in the structural behavior is analyzed in order to obtain the risk spectra associated to a specific seismic hazard and structural vulnerability. Thus the assessment of the seismic demand associated to any level of performance, which can be used either to design new structures or evaluate existent structures.